with our free apps for iPhone, iPad and Android

Get Started

Already have an account?

Log In

Chapter 3: Multi-Step Equations and
Inequalities
by S S
# Chapter 3: Multi-Step Equations and
Inequalities

## 3.4: Solving inequalities using Addition or
Subtraction

### Vocabulary

### Examples:

## 3.3: Solving equations with variables
on both Sides

### Note:

### Example:

## 3.1: Solving Two-Step Equations

### Examples:

### Definition

## 3.2: Solving equations having like terms
and parenthesis

### Examples :

## 3.5: Solving inequalities using Multiplication and
Division

### Examples

## 3.6: Solving multi-step equations

### Examples:

0.0 stars - reviews
range from 0 to 5

Inequality: A mathematical symbol formed by placing an inequality symbol between the two expressions.For example greater than, less than, greater or equal to, or less than or equal to. Solution of an inequality: The set of all numbers that produce true statements when substituted for the variable in the equation.

Example 1: m+5>=10 Write original equation m+5-5>=10-5 Subtract 5 from each side m>=5 Example 2: -10>x-12 Write the original eqution -10+12>x-12+12 Add 12 to each side 2>x Simplify

Try to put the variable on one side of the equation!

Example 1: 7n-5=10n+13 Write original equation 7n-5-7n=10n+13-7n Subtract 7n from each side -5=3n+13 Simplify -5-13=3n+13-13 Subtract13 from each side -18=3n Simplify -18/3=3n/3 Divide each side by 3 -6=n Simplify

Example 1: 3x + 7= -5 Write original equation. 3x + 7-7 = -5 -7 Subtract 7 from each side 3x=-12 Simplify 3x/3=-12/3 Divide each side by 3 x=-4 Simplify Example 2: 7-4y=19 Write th original equation 7-4y-7=19-7 Subtract 7 from each side -4y=12 Simplify -4y/-4=12/-4 Divide each side by -4 y=-3 Simplify

Two step Equations are simply equations that are solved in two steps trying to solve for the variable, using addition property of equality, subtraction property of equality, division property of equality , and multiplication property of equality.

Example 1: 5.20n+0.80n+47=377 Substitute 6.00n+47=377 Combine like terms 6n+47-47=377-47 Subtract 47 from each side 6n=330 Simplify 6n/6=330/6 dive each side by six n=55 Example 2: -21=7(3-x)=12 Write original equation -21=21-7x Distributive property -21-21=21-7x-21 Subtract 21 from each side -42=-7x Simplify -42/-7=-7/-7 Divide seven from each side x=3 Simplify

Like terms

Example 1: m/-3>3 Write original inequality -3 *m/-3 m Example 2: -10t>=34 Original inequality -10t/-10 t

Example1: 88+10g>138 Substitute 88+10g-88>138-88 Subtract 88 from each side 10g>50 Simplify 10g/10>50/10 Divide each side by 10 g>5 simplify Example 2: x/-4-6>=-5 Original inequality x/-4-6+6>=-5+6 Add six to each side x/-4>=1 Simplify -4*x/-4 x